Penerapan Teknologi Virtual Reality Metaverse pada Pendidikan Anak Usia Dini - Wahyudin, Achmad Yudi; Santosa, Alfarez; Febryansyah, Rido (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
Metaverse is a term that refers to the virtual world where the user can perform various activities and create a simulation like in the real world. Metaverse is a three-dimensional virtual space technology innovation that is currently making many people curious, both from its very rapid development and its implementation which is starting to be widely used in various sectors of life. This research study discusses how to apply virtual metaverse technology in early childhood education, where this method is expected to help in the world of education, especially in early childhood who need more attention and can answer various problems in the world of education in an effort to improve the quality of education in the world. Indonesia. The method used is taken from the research site and from several sources and journals relevant to the metaverse from 2020-2022 on the internet. The average use of Metaverse is used at the high school level and at the university level. However, by implementing this technology for early childhood education, this can benefits Indonesian education in the next 10 to 15 years. This study shows how metaverse can be implemented in the classroom. Teachers were encouraged to following several steps to integrate virtual reality game for students. This community service highlighted that the implementation of metaverse was feasible and potential for the teachers.